GLOBAL INTEGRATION OF SUPPLY CHAINS IN TEXTILE/APPAREL INDUSTRY - Salman, Muhammad (2006)
Supply chain management is important. It basically deals with the interconnection of an organization between the different processes that produce value in the form of products and services to the ultimate consumer. The final customer has the only real currency in the supply chain (Nigel S, Stuart C, Robert J; 2001). It has been established that effective supply chain management enables good and services to be produced more efficiently. This project is aimed to investigate the integration of the whole supply chain of textile/clothing industry from textile dyeing/printing industry to retail via clothing manufacturing (stitching) and buying and distribution agents. It covers the problems associated with the integration of all the partners and also endow with the proposal for improvements.